Dynamics of Mood Swings during Menstrual Cycles between Physically active and Inactive Adolescents: A Tripura-based Study - Krishnendu Dhar; SM Farooque; Nongmaithem Sneha Devi (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The menstrual cycle is an important biological process in women that is associated with a range of physical symptoms that can shape how women think, feel, and participate in daily life activities. This study employed a qualitative survey design to investigate the effect of physical activity and menstrual cycle on mood variability in adolescents. Purposively, 40 participants from Tripura University (n=20, physically active and n=20 Inactive) completed the Brunel mood scale questionnaire that explored menstrual cycle events: anger, tension, depression, fatigue, confusion, happiness and calmness. The participants’ response was further analysed descriptively through percentage analysis and differences between physically active and inactive students were assessed using the Mann Whitney-U test. The descriptive results depicted a mean rank of 16.20 and 24.80 of mood swing among Physically Active Students and Physically Inactive students respectively which shows a higher mood swing in inactive women. The significant difference was observed between physically active students and physically inactive students (two groups as U-value was 114.000 which was smaller than the critical value i.e., 127). Persons involved in physical activity have less chance of mood swing compared to sedentary people. In addition, the study concluded that regular moderate exercise helps reduce factors that enhance mood swing during the menstrual cycle.